Critical Analysis of The Rejection of Richard Bell's Thoughts on The Translation of The Qur'an in The Context of Orientalism - Abiyusuf, Ilham; Hafizi, Muhammad; Pakhrurrozi, Pakhrurrozi; Saputra, Wahyu; Hermanto, Edi (INJIES: Journal of Islamic Education Studies, 2024)
Richard Bell is a well-known English orientalist who focuses his research on the Qur'an with a critical academic approach. Bell's approach involves methods of historical, linguistic, and critical analysis to understand the Quran in historical and cultural contexts. However, this approach raises rejection from Muslim scholars who believe that the Bell method is inadequate to understanding the true meaning of the Quran as divine revelation. this study is to study the rejection of the approach of Richard Bell in the interpretation of the Qur'an by Muslim scholars and scientists. The main objective is to understand the basics of the arguments used in this denial and to evaluate its compatibility with the basic principles in interpreting the Quran according to the Islamic tradition. This research methodology uses a qualitative approach with methods of document analysis. Data is obtained from literature that deals with the works and approaches of Richard Bell, as well as texts that explain the views of Muslim scholars and academics on the interpretation of the Qur'an. The analysis was conducted to identify points of rejection of the Bell method and to evaluate the underlying arguments. Muslim scholars reject Richard Bell's approach to the Quran because they believe it doesn't fully respect the Quran as divine revelation. They think his methods are too focused on history and criticism, not capturing the Quran's true meaning. They prefer interpretations that consider the context of revelation, Prophet Muhammad's explanations, and see the Quran as a unified whole. They also doubt Bell's historical criticism and say Western academic methods have limits in understanding religious texts. Overall, they find Bell's approach doesn't fit Islamic principles of Quran interpretation.The rejection of Richard Bell's approach to the interpretation of the Qur'an is based on the belief that its historical and critical methods are insufficient to understand the true meaning of this sacred text.